»De phantastiske forskruede Forestillinger«. Introduktioner til Socialisme og Kommunisme i Danmark før 1848 - Nygaard, Bertel (Historisk Tidsskrift, 2009)
»These Warped Fantasies« Introductions to Socialism and Communism in Denmark before 1848 Already at the beginning of the 1840s, long before the socialist movement actually arose in Denmark, ‘socialism’ and ‘communism’ as concepts and as ways of thinking had been introduced to the Danish public, mainly through liberal and radical newspapers. These new currents noted and challenged the social exclusiveness and the extinction of a historical perception of future civilization that were embedded in the idealization of contemporary bourgeois society and its public. The very presentation of these concepts spelled a clash with the prevailing socio-theoretical and universalistic historiographical foundations of the elite culture. The principal outcome was the creation in the politico-ideological landscape of new dimensions developing through reciprocal differentiation. Among other things, the debate over these new concepts contributed to a clarification of both the liberal opposition’s attitude towards the social question and the emerging radical opposition’s attitude towards the liberal ideas and mindframe from which it arose. The introduction of socialism and communism as basic politcal concepts into a Danish context influenced the formation of a triangular ideological landscape of conservative, liberal and radical approaches that can be seen as characteristic of the modern epoch. Translated by Michael Wolfe